93.9k views
4 votes
|2)-6(-5a+6) = a+ 22

1 Answer

4 votes

Answer:

56/29

Explanation:

Let's solve your equation step-by-step.

2−6(−5a+6)=a+22

Step 1: Simplify both sides of the equation.

2−6(−5a+6)=a+22

2+(−6)(−5a)+(−6)(6)=a+22(Distribute)

2+30a+−36=a+22

(30a)+(2+−36)=a+22(Combine Like Terms)

30a+−34=a+22

30a−34=a+22

Step 2: Subtract a from both sides.

30a−34−a=a+22−a

29a−34=22

Step 3: Add 34 to both sides.

29a−34+34=22+34

29a=56

Step 4: Divide both sides by 29.

29a

29

=

56

29

a=

56

29

User Kris Verlaenen
by
5.3k points